Hair glucocorticoids during pregnancy in the context of trauma exposure and their predictive value for the development of childbirth-related posttraumatic stress disorder symptoms. (February 2023) - Steudte-Schmiedgen, S.; Schälicke, S.; Bergunde, L.; Karl, M.; Weise, V.; Junge-Hoffmeister, J.; Schumacher, S.; von Soest, T.; Weidner, K.; Kirschbaum, C.; Garthus-Niegel, S.
Abstract: Background: Childbirth-related posttraumatic stress disorder (CB-PTSD) is gaining attention as a mental disorder with negative sequela for mothers and their offspring. Maternal trauma history is a well-known vulnerability factor for CB-PTSD symptoms (CB-PTSS). Furthermore, alterations of the hypothalamus-pituitary-adrenal axis have been linked to both trauma exposure and PTSD development. Hence, we investigated whether trauma history was associated with long-term glucocorticoid (GC) levels during pregnancy and their predictive role for CB-PTSS. Further, we examined whether GCs act as a mediator in the relationship between trauma history and CB-PTSS and whether this was moderated by the subjective birth experience. Methods: 212 women participating in the prospective cohort study DREAMHAIR provided hair samples for quantification of long-term integrated cortisol and cortisone levels prior to their anticipated birth date accompanied by measures of trauma history. CB-PTSS and subjective birth experience were assessed two months postpartum. Findings: Trauma history predicted elevated hair cortisol and hair cortisone during the third trimester of pregnancy, however associations did not remain significant when Bonferroni correction due to multiple testing was applied. Trauma history also predicted higher CB-PTSS. Hair GC levels during pregnancy neither predicted CB-PTSS two months after birth nor mediated the relationship between trauma history and CB-PTSS. The subjective birth experience moderated the relationship of hair cortisol and cortisone with CB-PTSS. Conclusion: Our data suggest that a history of trauma contributes to a higher risk to develop CB-PTSS and elevated long-term GC levels during the third pregnancy trimester. Further, the predictive role of hair cortisol and cortisone levels for CB-PTSS may depend on subjective birth experience. This highlights the need to consider the latter in future investigations when examining the role of stress-related biomarkers in more severely affected samples. Highlights: Investigation of risk factors for childbirth-related PTSD symptoms (CB-PTSS). Trauma history predicted higher CB-PTSS two months postpartum. Trauma history predicted elevated hair glucocorticoids (GCs) during pregnancy. The predictive value of hair GCs for CB-PTSS depended on the subjective birth experience.